2023
DOI: 10.3390/jcm12020534
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Multi-Mode Monophasic Stimulation with Capacitive Discharge on the Facial Nerve Stimulation Reduction in Young Children with Cochlear Implants: Intraoperative Recordings

Abstract: Facial nerve stimulation (FNS) is a potential complication which may affect the auditory performance of children with cochlear implants (CIs). We carried out an exploratory prospective observational study to investigate the effects of the electrical stimulation pattern on FNS reduction in young children with CI. Ten ears of seven prelingually deafened children with ages up to 6 years old who undergone a unilateral or bilateral CI surgery were included in this study. Electromyographic (EMG) action potentials fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The asymmetric profile obtained for BP agrees with that reported in previous works (Rattay et al 2001, Hanekom 2005, Dang 2017), in addition to the negative lobes exhibited by TP at the sinking return electrodes (Kalkman et al 2015, Dang 2017, Cakmak 2022. Current focusing strategies such as BP and TP required more electric current to achieve similar peak voltage levels (figures 4(a) and (b)), as reported elsewhere.…”
Section: Intracochlear Voltagessupporting
confidence: 90%
See 1 more Smart Citation
“…The asymmetric profile obtained for BP agrees with that reported in previous works (Rattay et al 2001, Hanekom 2005, Dang 2017), in addition to the negative lobes exhibited by TP at the sinking return electrodes (Kalkman et al 2015, Dang 2017, Cakmak 2022. Current focusing strategies such as BP and TP required more electric current to achieve similar peak voltage levels (figures 4(a) and (b)), as reported elsewhere.…”
Section: Intracochlear Voltagessupporting
confidence: 90%
“…In order to gain a better understanding of the underlying biophysics of CI electrical stimulation, the use of computational models have increasingly gained the attention of researchers. This is the case of volume conduction or volume EF models, which, based on general or user-specific anatomical models of the cochlea, permit the prediction of the EF and current density using numerical techniques such as the finite element method (FEM) (Rattay et al 2001, Wong et al 2015, Hanekom and Hanekom 2016, Kalkman et al 2016, Nogueira et al 2016, Teal and Ni 2016, Dang 2017, Gerber et al 2017, Mangado López et al 2018b, Potrusil et al 2020, Sriperumbudur et al 2020, Cheng et al 2022, Hrncirik et al 2023. However, models restricted to the cochlea present the limitation that they do not realistically emulate boundary conditions and cannot be used for the analysis of extracochlear current flow through head tissues.…”
Section: Introductionmentioning
confidence: 99%
“…For users presenting with FNS, audiologists may first attempt to control the problem by re-programming the device to produce lower currents, followed by turning off offending electrodes-both of which can reduce speech comprehension [4]. If these solutions fail, clinics have observed that re-implantation with an Oticon Medical Neuro Zti implant can resolve FNS issues [8,[10][11][12][13]. Indeed, for our two subjects, re-implantation with the Oticon Medical device not only completely resolved FNS but also improved speech recognition [8].…”
Section: Discussionmentioning
confidence: 99%